Nutritional Status of Children Under Five Years of Age and Factors Associated in Padampur VDC, Chitwan - Ruwali, D (Health Prospect, 2018)
Background: Malnutrition is a major underlying cause of the child morbidity and mortality in Nepal. Factors that contribute to malnutrition are many and varied, so multifaceted strategies are required to combat it. It is therefore important to determine its causative factors before appropriate intervention can be implemented. This analysis tries to analyze the factors associated with nutritional status among children of under five years of age so that nutritional intervention can be better designed. Methodology: A community based cross-sectional descriptive survey using a structured questionnaire and measurements of weight and height to determine the nutritional status of underfive children and factors associated with it. A structured questionnaire was then administered to the mothers in their home settings. Anthropometric measurement was then used to determine if children were underweight (weight-for-age), wasting (weight-for-height) and stunting (height-for-age) based on CDC/WHO reference. Logistic regression statistical tool was used to analyze the influence of different predictors. Results: Prevalence of underweight, stunting and wasting was 22.7%, 37.3% and 25.7% respectively. Study indicated that the risk of stunting increases with age. Socioeconomic status was most important factors associated with stunting, underweight and wasting. Meeting the minimum dietary diversity, minimum meal frequency and minimum acceptable diet was associated with better nutritional status of children. Conclusion: Results of this study indicate that undernutrition is still an important problem among children under five years of age in Padampur VDC, Chitwan. Furthermore, this malnutrition was found to be a result of maternal, socio-economic and child individual factors. DOI: http://dx.doi.org/10.3126/hprospect.v10i0.5639 Health Prospect Vol.10 2011, pp.14-18